How sweet it was [videorecording (DVD)] : the sights and sounds of gospel's golden age. - Campbell, Delois Barrett, 1926-2011; Tharpe, Rosetta, 1915-1973; Bradley, J. Robert (John Robert), 1920-2007; Renfro, Jessie Mae, 1921-1996; Williams, Marion, 1927-1994; May, Brother Joe, 1912-1972; Griffin, Bessie, 1923-1989; Coates, Dorothy Love; Andrews, Inez; Bradford, Alex; Cleveland, James (Shanachie Entertainment Group, 2010)
A best of the best compilation covering a span of over 40 years. Compiled by gospel music expert Anthony Heilbut, this exciting multi-faceted package offers great film of gospel icons, filmed in the 1960s, as well as many all-time classic music tracks from the 1940s-1960s on the accompanying CD. Also includes booklet with biographical notes and photos.